The Potential of A Balinese Traditional Medicine Kelor Leaves (Moringa oleifera) For Male Infertility Treatment : A Mini Review - Luh Putu Widiastini; I. G. Agung Manik Karuniadi; I Nyoman Mangku Karmaya; I Gede Widhiantara (Institute of Medico-legal Publications Pvt Ltd, 2022)
Infertility is one of the causes of reproductive welfare disorders of married couples around the world.One of the causes of infertility at the molecular level is Oxidative Stress (OS) because the products ofReactive Oxygen Species (ROS), both endogenous and exogenous, exceed the levels of antioxidants inthe body. The aims of this review is to find out the potential of traditional medicinal from Bali, Indonesiawith local name Kelor (Moringa oleifera) leaves in preventing the occurrence of potential infertilityin men based on the results of research in vivo using animal trials. The method used by the writer is aliterature study.The results of this literature review found that kelor/moringa had a positive effect onsexual behavior, especially an increase in libido. In addition, it has a positive effect on spermatogenesis,the quality of spermatozoa especially increases sperm motility, sperm count/volume, germ cell count,renews endogenous antioxidant enzyme activity, reduces levels of ROS, and provides a protectiveeffect on the testes from damage. Moringa oleifera contains many free radical blocking molecules.Some phytochemical test results show that moringa contains powerful antioxidants, including alkaloids,flavonoids, saponins, triterpenoids/steroids, tannins.